Teachers' Efforts to Overcome Anxiety When Learning Arabic in Grade 8 MTSN 3 Nganjuk - Zunairoh, Yuyun; Fauzi, Eidil (UIN Syekh Wasil Kediri, Indonesia, 2021)
Learning Arabic as a second language requires effort and a high idea, especially for the novice learner. Students feel difficulty and fear of linguistic errors. This feeling of anxiety is said when learning Arabic. The objectives of the research are to know the level of students' anxiety (anxiety), to find out the reasons for students' anxiety, and to know the teacher's efforts to solve students' anxiety when learning the language. This research is a mixed research between quantitative and qualitative in a squential explanatory design. The method of data collection is: questionnaire, interview, documents. A sample of 67 students. Research results: Two students had no anxiety when learning Arabic, 10 students felt mild anxiety, 4 students felt moderate anxiety, 25 students felt severe anxiety, and 26 students felt most anxious when learning Arabic. The reasons mean that some of them memorize a few vocabulary, do not understand the subject of the Arabic language, and feel difficulty in interpreting the Arabic sentence, and they do not like to learn the Arabic language. The teacher’s efforts to solve students’ anxiety when learning the Arabic language is that the teacher knows the types of students’ learning background, uses simplified learning conditions, the teacher develops language games, and gives the teacher a separating factor as an ice break game when teaching, and the teacher gives the study material according to the students’ competence, and the teacher maintains social relations Close with students when teaching